2010
DOI: 10.1007/s11130-010-0158-4
|View full text |Cite
|
Sign up to set email alerts
|

Pomological and Nutraceutical Properties in Apricot Fruit: Cultivation Systems and Cold Storage Fruit Management

Abstract: We have investigated the effect of cultivation systems and fruit post-harvest management on the antioxidant properties of apricot fruits. Trees of five cultivars 'Tyrinthos', 'Cafona', 'Bella d'Italia', 'Vitillo' and 'Pellecchiella' were cultivated under integrated and organic systems. Fruits were collected at full maturity stage and analyzed either immediately or after storage at 4+/-0.5 degrees C and 85% of relative humidity for seven and 14 days. The main pomological traits (weight, colour, flesh firmness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
36
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 40 publications
10
36
1
1
Order By: Relevance
“…'Harcot' and 'Aleksandar' exhibited the lowest antioxidant power, whereas the highest value observed in 'Roxana'. This is in accordance with the reports of Drogoudi et al [33], Kalyoncu et al [9], Schmitzer et al [47], Hegedüs et al [14] and Leccese et al [18,42] who also reported a large variation of total phenolic and flavonoid content and antioxidant activity for apricot cultivars due to their geographical origin. Additionally, total phenolic content seems to be a good indicator of the antioxidant potential in fruit and authors report correlation between these parameters in different fruit species, including apricot [45,47].…”
Section: Phenolic Content and Antioxidant Capacitysupporting
confidence: 92%
See 3 more Smart Citations
“…'Harcot' and 'Aleksandar' exhibited the lowest antioxidant power, whereas the highest value observed in 'Roxana'. This is in accordance with the reports of Drogoudi et al [33], Kalyoncu et al [9], Schmitzer et al [47], Hegedüs et al [14] and Leccese et al [18,42] who also reported a large variation of total phenolic and flavonoid content and antioxidant activity for apricot cultivars due to their geographical origin. Additionally, total phenolic content seems to be a good indicator of the antioxidant potential in fruit and authors report correlation between these parameters in different fruit species, including apricot [45,47].…”
Section: Phenolic Content and Antioxidant Capacitysupporting
confidence: 92%
“…Differences among above four cultivars were not significant, and also between 'Harcot' and 'Roxana'. Likewise, previous studies reported variable ranges of SSC [18,19,23,33]. Regarding acidity content, remarkable differences were found among cultivars, being the highest in 'Roxana', and the lowest in 'Vera'.…”
Section: Soluble Solids Content and Acidity Levelsupporting
confidence: 51%
See 2 more Smart Citations
“…The antioxidant profile of apricot fruit (Prunus armeniaca L.) has recently been analysed with particular reference to the total antioxidant capacity, polyphenols and carotenoids [5][6][7][8][9]. Given that a diverse germplasm exists for this species, the effect of the genotype on antioxidant properties has been considered, and the nutraceutical profiles of many cultivars have been studied in order to find outstanding genotypes rich in antioxidant compounds [10][11][12].…”
Section: Introductionmentioning
confidence: 99%